الإحساس بالمكان في الفضاءات العامة لمراكز التسوق من وجهة نظر المتسوقين - جمال الأحمر; لين ونوس (Tishreen University, 2019)
The research aims to study the most important factors that enhance the sense of place from Visitors׳ perceptions within the public spaces of shopping malls in the cities of the Syrian Coastal area. The research used the method of the questionnaire which conducted in Tartous Mall in Tartous and Orange Mall in Lattakia. The data were analyzed according to the descriptive statistics analysis. The results showed that the important design factors considered by visitors are legibility, social image and interaction, the ambience and  the decoration. Furthermore, the result of the open question showed the importance of organizing events. Also, the importance of event theme decoration (event ambience), as well as the harmony of the commercial facades that form the vertical boundaries of the public spaces. يهدف البحث إلى دراسة أهم العوامل التي تعزز الإحساس بالمكان من وجهة نظر المتسوقين ضمن الفضاء العام لمراكز التسوق في مدن الساحل السوري. اعتمد البحث على منهجية الاستبيان حيث جرى الاستبيان في كل من طرطوس مول  في طرطوس و أورانج مول في اللاذقية, و تم تحليل البيانات وفق أداة الإحصاءات الوصفية. كما أظهرت النتائج أن العوامل الهامة للتصميم من وجهة نظر الزوار هي الوضوح والصورة الاجتماعية والتفاعل و عوامل الجو المحيط و التصميم الداخلي. كما أظهرت نتيجة السؤال المفتوح أهمية تنظيم الأحداث والاحتفالات, وكذلك أهمية التصاميم و التزيينات الخاصة بموضوع الحدث أو الاحتفال (جو الحدث), بالإضافة إلى تناغم الواجهات التجارية التي تشكل الحدود الرأسية للفراغات العامة.